Efficacy of tildrakizumab by patient demographic and disease characteristics across a phase 2b and 2 phase 3 trials in patients with moderate‐to‐severe chronic plaque psoriasis. (9th February 2020) - Poulin, Y.; Ramon, M.; Rosoph, L.; Weisman, J.; Mendelsohn, A.M.; Parno, J.; Rozzo, S.J.; Lee, P.
Abstract: Background: Tildrakizumab is a high‐affinity, anti‐interleukin‐23p19 monoclonal antibody approved for treatment of moderate‐to‐severe plaque psoriasis. Objectives: To evaluate the effects of patient demographic and disease characteristics on tildrakizumab efficacy using phase 2b/3 trial data. Methods: Data from patients who received placebo, or tildrakizumab 100 or 200 mg, in P05495 [NCT01225731], reSURFACE 1 [NCT01722331] and reSURFACE 2 [NCT01729754] were analysed. Patient subgroups were defined by age, sex, race, weight, self‐reported psoriatic arthritis, failure of ≥1 traditional systemic treatment and prior biologic use. Percentage of Psoriasis Area and Severity Index (PASI) 75 and 90 responders at Week 12 were compared across treatment arms in each subgroup. Absolute PASI at Weeks 0 and 12 was also determined for each subgroup. Results: Among patients randomized in P05495 ( N  = 355), reSURFACE 1 ( N  = 772) and 2 ( N  = 1090), percentage of PASI 75 and 90 responders were significantly greater for each tildrakizumab dose vs. placebo ( P  <   0.0001). PASI 75 and 90 responder percentages were numerically greater in patients <65 years of age, bodyweight ≤90 kg, without psoriatic arthritis and with no prior biologic exposure (only PASI 90), vs. their counterparts in corresponding subgroups. There were no clear or consistent differences in efficacy between the other subgroups. Absolute PASI scores were generally similar across subgroups. Conclusions: Small numerical differences in tildrakizumab efficacy were observed between subgroups defined by patient age and weight, presence of psoriatic arthritis and prior biologic use. These differences were not clinically meaningful; however, analyses of long‐term data may be of value. Tildrakizumab efficacy did not differ with respect to patient sex or race, or number of prior failed conventional systemic treatments. Overall, these results suggest tildrakizumab may be appropriate for treatment of moderate‐to‐severe plaque psoriasis in patients with a range of demographic and disease characteristics.